Distinctive Bimetallic Oxides for Enhanced Catalytic Toluene Combustion: Insights into the Tunable Fabrication of Mn−Ce Hollow Structure. Issue 10 (2nd April 2020) - Li, Lei; Zhang, Changyu; Yan, Jinlong; Wang, Dong; Peng, Yue; Li, Junhua; Crittenden, John
Abstract: The hollow structured Mn−Ce binary catalysts were facilely prepared utilizing carbon microsphere as templates. Based on acid/alkali‐pretreatment of the carbon templates, the Mn−Ce shell structure and surface components were facilely. The MnCe−OH catalyst, obtained from the alkali‐treated carbon sphere, showed the highest catalytic performance for toluene combustion with T90 (the temperature for 90 % toluene conversion) of 237 °C at a space velocity of 36, 000 mL/(g ⋅ h). The according specific rate is 4.8*10 −9 mol/(m 2 ⋅ s) and the lower active energy value is 98.9 kJ/mol. With the aid of various characterizations, it indicates that the thinner and porous shell should accounted for the enhanced activity, which provided enriched accessible active sites and enhanced mass transfer for reactants. The abundant surface‐active oxygen (48.8 %) and the interaction between Ce and Mn species also benefited the superior catalytic performance. Additionally, a possible reaction pathway was provided in terms of the in‐situ DRIFTS study, revealing that the toluene molecules transformed into aldehydic, then into benzoate species, and finally formed CO2 and H2 O. Abstract : Ceriously hollow : The hollow structured Mn−Ce binary catalysts were facilely prepared utilizing carbon microsphere as templates. The thinner shell of Mn−Ce oxides were fabricated by treating the carbon templates with alkali/acid, which provided enriched accessible active sites and enhanced mass transfer for reactants. This tunable strategy pave a way to regulate microstructure of hollow structural catalyst with an enhanced catalytic performance.